BandEst: Measurement-Based Available Bandwidth Estimation and Flow Admission Control Algorithm for Ad Hoc IEEE 802.15.4-Based Wireless Multimedia Networks. (22nd March 2015) - Farooq, Muhammad Omer; Kunz, Thomas
Abstract : We highlight different important factors that must be considered for an effective available-bandwidth-based flow admission control algorithm in ad hoc wireless networks. Moreover, we present BandEst; it is a combination of a measurement-based available bandwidth estimation technique and a flow admission control algorithm for ad hoc IEEE 802.15.4-based ad hoc networks that considers the identified factors. Extensive simulations are performed to compare BandEst with the state-of-the-art available-bandwidth-based flow admission control algorithms for ad hoc wireless networks. Our simulation results demonstrate that BandEst significantly outperforms the state-of-the-art available-bandwidth-based flow admission control algorithms for ad hoc wireless networks.